THE SURVIVAL OF SRADHA BHAKTI AS A HINDU FORTIFICATION IN MENJING VILLAGE - I Made Wirahadi Kusuma; I.B.G. Yudha Triguna; I Wayan Winaja (UHN I Gusti Bagus Sugriwa Denpasar, 2023)
Multiculturalism and pluralism stem from the development of people; nonetheless, human distinctions persist based on their patterns and ideas. Pancasila is the shield of Indonesia's culture, which is comprised of several tribes, ethnicities, and faiths bonded together by customs and culture. In the decades of the modern period, a lack of intercultural education, moral problems, and communal values have led to numerous cases. This study employs qualitative methodologies and descriptive qualitative analysis. The set of procedures includes data reduction, data presentation, data verification, and data interpretation. The contradictions in Menjing Village continue to be a political and ideological fight that undermines public trust. The strategies for sustaining sraddha bhakti in Menjing are enhancing social and religious capital via community empowerment, using the likelihood of the political society's processes, including the cultural factor as a rule for social and religious life, enhancing the structural dimension via the institution system, conducting programs for the advancement of religious education based on conservatism, the religious education system in Menjing, comprises components of religious education beliefs, religious practices in religious education, religious experience in religious education, religious knowledge as a means of bolstering the Hindu religious spirit, and religious education outcomes.